Association Between Indices of Body Composition and Metabolically Unhealthy Phenotype in China: A Cross-Sectional Study - Lv, Fang; Cai, Xiaoling; Li, Yufeng; Fu, Zuodi; Zhang, Xiuying; Zhou, Xianghai; Han, Xueyao; Ji, Linong (Frontiers in Endocrinology, 2022)
Introduction: Body composition is closely related to metabolic health status. Visceral adipose tissue (VAT) dysfunction contributes to metabolic syndrome. However, results regarding subcutaneous adipose tissue (SAT) and skeletal muscle are controversial. We aimed to determine the association of indices of body composition with abnormal metabolic phenotype in China. Methods: A total of 3, 954 subjects (age 50.2±11.7 years) with body mass index (BMI) more than 18.5 kg/m2 from Pinggu Metabolic Disease Study were analyzed. Quantitative computed tomography metabolic status (QCT) was performed to measure total adipose tissue (TAT), VAT, SAT area, and lumbar skeletal muscle area (SMA). Participants were divided into six groups on the basis of BMI category (normal weight/overweight/obesity) and metabolic status (healthy/unhealthy), as defined by the presence or absence of components of the metabolic syndrome by Chinese Diabetes Society criteria. Results: 63.4%, 39.5%, and 23.3% participants were classified as metabolically healthy phenotype in individuals with normal weight, overweight and obese, respectively. Individuals in the highest TAT, VAT, and VAT/TAT ratio category had higher risk of being metabolically unhealthy than individuals in the lowest group (all p＜0.01). While, risk for metabolically unhealthy was reduced significantly in the highest SMA/TAT ratio category when compared with the lowest category in individuals with normal wight and overweight (both p＜0.05). Risk for metabolically unhealthy was reduced significantly in the highest SAT category when compared with the lowest category (OR=0.555, 95%CI: 0.360-0.856, p=0.008) in individuals with obese after adjustment for age, sex and BMI. However, skeletal muscle index (SMI) showed no significant association with the metabolically healthy status in different BMI categories (p＞0.05). The VAT and VAT/TAT ratio were better diagnostic values of indicators to differentiate metabolically unhealthy subjects from controls compared with other indicators, such as TAT, SAT, SMI, SMA/TAT ratio. Conclusions: Higher visceral adipose tissue was closely associated with metabolically unhealthy phenotype in Chinese adults. Subcutaneous adipose tissue might be an protective factor for metabolic health status only in obese individuals.